Normal levels of some macro-and micro-minerals and hormones in the ovarian tissues of pregnant and cyclic buffaloes (Bubalus bubalis) - Bhardwaj, R L; Roy, K S; Srivastava, A K (The Indian Journal of Animal Sciences, 2012)
The concentrations of some important macro-and micro-minerals and hormones were estimated in ovarian tissues of cyclic and pregant bufaloes. In ovary of cyclic animals the levels of magnesium, calcium, iron and zinc were 46.4+3.64, 16.0 ± 0.73, 11.1 ± 0.80 and 2.45 ± 0.19 g.g-l, respectively. whereas in ovary of pregnant animals these concentrations were 52.0 ± 3. 13. J 7.4 ± 1.33, 12.4 ± 1.68 and 2.69 ± 0.21 µg.g-1, respectively. The levels of progesterone, estradiol 17-ß and follicular stimulating hormone in follicular fluid of cyclic buffaloes were 39.17 ± 0.31, 4.51 ± 0.78 and 1.58 ± 0.16 µg.ml-1respectively.